Quantitative Evaluation of the Impact of Novartis Knowledge Center Information Services in Drug Discovery and Development - He, Leifang; Juterbock, Deborah (Qualitative and Quantitative Methods in Libraries, 2017)
Novartis Knowledge Center’s (NKC) VALUE (Value Assessment on Library Utilization Efficiency) initiative was created to determine the value of its information services (via its e-library model) in supporting the Novartis  mission of bringing innovative drugs to patients and its business drivers for  innovation, growth and productivity.   To evaluate the business impact and outcomes of NKC’s delivered information services on drug discovery, drug development and marketing at Novartis, NKC enterprise-wide customer satisfaction surveys were conducted in 2008 and 2011.   Using the survey data, we examined service relevancy (how NKC services align to Novartis overall strategies and top objectives), efficiency (how quickly and easily NKC customers obtain information relevant to their decision making), and the return on Novartis investment in the NKC.  The 2011 survey data results validated that NKC is on track in executing its e-library model strategies, but caution on keeping up with the growing user population.